Efforts To Counter Terrorism Crimes In Indonesia - Yolla Veronica Sembiring; Yasmirah Mandasari Saragih; Muhammad Azhali Siregar; Muhammad Mujahidin ZA; Wildan Fahriza (International Journal of Law, Crime and Justice, 2024)
Indonesia needs to get rid of terrorism once and for all. This journal aims to describe and analyze using the approach of various efforts to counter terrorism crimes in Indonesia. The research method used in this study uses a descriptive qualitative approach to present an overview of terrorism and several strategies to combat this crime in Indonesia. The formulation of the problem based on the description of the background above is as follows: what are the factors of terrorism crimes in Indonesia and how to overcome terrorism crimes in Indonesia. Terrorism is a disturbing phenomenon. Efforts to counter terrorism crimes carried out by the Government are implemented through repressive efforts. There are five factors that cause terrorism crimes in Indonesia, namely: tribalism, nationalism/separatism, poverty and inequality and globalization, non-democracy, violations of human dignity and religious radicalism.